The Role of Productive Families' Ads on Facebook to push the Final Consumers to make Purchasing Decision in KSA - Alafeef, Mahmoud Abdel Muhsen Irsheid (Archives of Business Research, 2019)
This current study aimed to reveal the role of productive families' ads on facebook to push the final consumers to make purchasing decision in KSA, and to achieve that researchers prepared two study tools; the first was to measure the level of productive families' products ads on facebook and consist of (32) items, and the second was to deduct the behavior of final consumers to make purchasing decision and consist of (31) items that were distributed on (5) dimensions, which are : role to reach the final consumer mind and has (6) items, achieve convictions and contentment about the product of final consumer and has (6) items, meet the needs of final consumer and has (7) items, fulfill the desires of final consumer and has (6) items, and push final consumer to make the purchasing decision and has (6) items, and were distributed after verifying its consistency and reliability on a random sample that consist of (329) customers. Results showed a role of productive families' ads on facebook to reach the final consumer mind in KSA, with (10.3%), a role of productive families' ads on facebook to achieve convictions about the product of final consumer in KSA, at (3.3%), a role of productive families' ads on facebook to meet the needs of final consumer in KSA, with (4.0%), a role of productive families' ads on facebook to fulfill the desires of final consumer in KSA, with (5.4%), and finally a role of productive families' ads on facebook to push the final consumer to make purchasing decision in KSA, with (6.7%).